Re-examining the too-big-to-fail problem for dark matter haloes with central density cores. Issue 3 (26th November 2014) - Ogiya, Go; Burkert, Andreas
Abstract: Recent studies found the densities of dark matter (DM) subhaloes which surround nearby dwarf spheroidal galaxies (dSphs) to be significantly lower than those of the most massive subhaloes expected around Milky Way-sized galaxies in cosmological simulations, the so-called too-big-to-fail (TBTF) problem. A caveat of previous work has been that dark substructures were assumed to contain steep density cusps in the centre of DM haloes even though the central density structure of DM haloes is still under debate. In this study, we re-examine the TBTF problem for models of DM density structure with cores or shallowed cusps. Our analysis demonstrates that the TBTF problem is alleviated as the logarithmic slope of the central cusp becomes shallower. We find that the TBTF problem is avoided if the central cusps of DM haloes surrounding dSphs are shallower than r −0.6 .